2016
DOI: 10.1007/s40272-016-0203-3
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Activated Factor VIIa (rFVIIa) Treatment in Very-Low-Birth-Weight (VLBW) Premature Infants with Acute Pulmonary Hemorrhage: A Single-Center, Retrospective Study

Abstract: rFVIIa administration was observed to be effective in stopping pulmonary hemorrhage, reducing blood product requirement, and improving coagulation test parameters. Prospective studies are needed to evaluate the efficacy, reliability, and long-term results of rFVIIa in the prevention and treatment of pulmonary hemorrhage in premature infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The survival group had more patients received plasma treatment, but multivariate logistic regression showed that plasma treatment did not increase survival. In the meantime, recent studies have also presented similar strategies, such as the using haemocoagulase or recombinant factor VII, as potential therapy for PH (18,19). By contrast, Usemann et al (20) found that infusion of FFP (10-20 mL/kg) within 4 hours increased the risk of pulmonary hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…The survival group had more patients received plasma treatment, but multivariate logistic regression showed that plasma treatment did not increase survival. In the meantime, recent studies have also presented similar strategies, such as the using haemocoagulase or recombinant factor VII, as potential therapy for PH (18,19). By contrast, Usemann et al (20) found that infusion of FFP (10-20 mL/kg) within 4 hours increased the risk of pulmonary hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to our data, the authors gave only one dose of aFVII and the clinical situation was complicated by circulatory failure secondary to the pulmonary hemorrhage. In the second [4], the authors found positive effects of aFVII on pulmonary bleeding but no effects on IVH. Thus, the success of aFVII treatment in progressing IVH may be essentially dependent on optimal timing, duration and dosing of treatment, as we discuss below.…”
Section: Discussionmentioning
confidence: 97%